2012
DOI: 10.1152/ajpendo.00381.2011
|View full text |Cite
|
Sign up to set email alerts
|

Sertoli-secreted FGF-2 induces PFKFB4 isozyme expression in mouse spermatogenic cells by activation of the MEK/ERK/CREB pathway

Abstract: In this study, we investigated how the hormonal regulation of spermatogenesis modulates 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFKFB) isozyme expression in two mouse spermatogenic cell lines, GC-1 spg and GC-2 spd (ts). For this purpose, TM4 Sertoli cells were used to obtain conditioned medium that was treated or not with dihydrotestosterone for 2 days [dihydrotestosterone conditioned medium (TCM) and basal conditioned medium (BCM), respectively]. We observed an increase in the expression of PFK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Several splice variants have been reported, with the PFK-2 core domain being conserved among all of them ( 162 , 164 ). The PFKFB4 gene encodes an isoenzyme that is expressed in the testis under the regulation of testosterone ( 165 , 166 ). Moreover, it has been demonstrated that PFKFB4 mRNA and protein levels are regulated by hypoxia and glucose levels in different cancer cell lines from the prostate, liver, colon, bladder, stomach and pancreas ( 86 , 87 , 167 171 ).…”
Section: Reprogramming the Glycolytic Phenotype Of Cancer Cellsmentioning
confidence: 99%
“…Several splice variants have been reported, with the PFK-2 core domain being conserved among all of them ( 162 , 164 ). The PFKFB4 gene encodes an isoenzyme that is expressed in the testis under the regulation of testosterone ( 165 , 166 ). Moreover, it has been demonstrated that PFKFB4 mRNA and protein levels are regulated by hypoxia and glucose levels in different cancer cell lines from the prostate, liver, colon, bladder, stomach and pancreas ( 86 , 87 , 167 171 ).…”
Section: Reprogramming the Glycolytic Phenotype Of Cancer Cellsmentioning
confidence: 99%
“…In total, 115 men who presented themselves to an infertility clinic were included in this study, as described below. A total of 66 men were recruited into the study (mean age AE SD, 25.09 AE 3.84 year; range, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], including 33 subfertile (oligoasthenozoospermia) men who attended the IVF lab for infertility treatment and 33 age-matched donor men with normal semen parameters (normozoospermia), and were analyzed by reverse transcription quantitative polymerase chain reaction (RT-qPCR).…”
Section: Patients and Samplesmentioning
confidence: 99%
“…In addition, some studies demonstrated that neuroprotective function increases the Bcl-2 level to an anti-apoptotic state and activates autophagy through the induction of silibinin through the Notch pathway [24]. ERK and NF-rB pathways are known to alter the expression of pro-apoptotic and antiapoptotic genes such as Bax and Bcl-2 by regulating the activity of transcription factors including CREB [25,26]. Therefore, MEK/ERK/CREB pathway is considered to play a critical role in apoptosis, but the regulation effect of silibinin on the MEK/ERK/CREB pathway remains unclear.…”
Section: Discussionmentioning
confidence: 99%